Role of Islamic Education Teachers in Shaping Students' Religious Character in the Digital Era: A Case Study of SDN 1 Kondangsari, Cirebon - Rochim, Ahmad Abdul; Amal Khayati (HEUTAGOGIA: Journal of Islamic Education, 2023)
This qualitative study explores the multifaceted role of Islamic Education (PAI) teachers in shaping students' religious character amid the digital era's challenges at SDN 1 Kondangsari, Cirebon. Employing a case study approach within a Field Research design, the research integrates semi-structured interviews, non-participant observations, and document analysis, analyzed through Miles and Huberman's interactive model to ensure a comprehensive understanding. The findings reveal that PAI teachers are facilitators, mentors, environmental providers, communicators, role models, evaluators, innovators, moral and political agents, cognitive agents, and managers in cultivating students' resilient, religious character. They adeptly utilize digital tools, instill Islamic practices through habituation, and embody exemplary conduct, equipping students to navigate modern society's intricacies. The study underscores the importance of integrating traditional religious teachings with digital advancements and calls for further research to assess these pedagogical strategies' broader applicability and long-term impact. The research highlights the critical need for continuous innovation in teaching approaches to bridge the gap between faith and technology, contributing to the field of religious education and societal development. The implications of this study underscore the necessity for comprehensive teacher training programs, supportive school environments, and collaborative efforts involving educators, parents, and the community in character-building initiatives.